Calypso Singers, Trinidad - (:unkn) unknown (My University, 2009)
Five minstrel singers. At the back of the postcard are the words: "Cunard Line: Largest and Fastest Ocean Liner in the world."
Colour: Black and white; Style: Landscape; Other: Bordered,Divided
Keywords: Postcards; Trinidad and Tobago; Minstrels--Trinidad and Tobago; Calypso musicians--Trinidad and Tobago; Costume--Trinidad and Tobago